Um estudo sobre a implantação da proteção social especial de média complexidade: contribuição à efetividade do SUAS: Campinas/SP - 2002/2010 - Sertório, Leniter Venância dos Anjos (2010)
This dissertation is the result of the research performed in the Municipal Secretariat of Citizenship, Social Assistance and Inclusion (SMCAIS) of Campinas/SP, with Special Social Protection of Medium Complexity implementation emphasis in CREAS and in Women, Elder and LGBT Reference Centers during the period between 2002 and 2010. The general purpose was to analyze the Special Social Protection of Medium Complexity implementation and its contribution to the SUAS effectiveness in Campinas/SP. The research subjects were the Social Assistants, Psychologists and Lawyers of the services which belongs to the Special Social Protection of Medium Complexity, its coordinators and the previous and current managers of the Social Assistance Policy. Sixteen (16) semi-structured interviews were conducted with them. It was defined as hypothesis that the implementation of Special Social Protection of Medium Complexity in Campinas is being developed in a progressive way, presenting possibilities and progress, as well as limits and challenges, contributing to the SUAS effectiveness. The methodology included bibliographic and documental research together with qualitative approach of field research besides the participant observation since the researcher works in the Social Assistance area. The content analysis technics to data interpretation was used in this research. The main conceptual references were Brazilian Social Policy, Social Assistance, Social Protection and Socio-Assistance Rights. The achieved results demonstrated that the Special Social Protection of Medium Complexity implementation dynamics is contributing to the SUAS effectiveness, expressing a permanent development and evolution